Words Matter. But Rights Matter More - Oberoi, Pia (Anti-Trafficking Review, 2018)
Response to the ATR Debate Proposition: ‘It is important and necessary to make clear distinctions between (irregular) migrants, refugees and trafficked persons.’ The international community has recently taken steps to agree two intergovernmental compacts, which together are intended to revitalise the global governance of migration and asylum. The Global Compact on Refugees seeks to strengthen international cooperation on the refugee regime, while the Global Compact for Safe, Regular and Orderly Migration aims to establish principles, commitments and understandings among Member States regarding international migration in all its dimensions. The compacts have been brought into existence against a backdrop of widespread and increasingly systematic human rights violations committed against migrants by state officials, traffickers and other criminals, and leading to what has been called ‘one of the greatest human tragedies of our time’. At the same time, the very bifurcation of the compacts into two ‘separate, distinct and independent’ agreements rests on a set of assumptions that could distort rather than illuminate the complex issue of contemporary human mobility.